Analisis profil dan masalah industri kecil dan rumah tangga: Studi kasus di Kabupaten Ngawi, Jawa Timur - Mudrajad Kuncoro; Kusumahadi Widjajanto (Universitas Islam Indonesia, 2001)
This paper attempts to analyse the development of small and home establishments (SCE) in Ngawi, one of districts in the East Java province. Java province, special attention is given to major characteristics and problems of SCE. The rapid growth of large and medium establishments (LME) since the 1970s has overshadowed the sluggish growth of SCE.